1985
DOI: 10.1016/s0735-1097(85)80430-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic demonstration of concealed conduction in anomalous atrioventricular bypass tracts

Abstract: To demonstrate the occurrence of concealed conduction in anomalous atrioventricular (AV) bypass tracts, 11 patients were selected for study. Two had a right-sided and nine had a left-sided bypass tract. Electrode catheters were placed in the right atrium, coronary sinus, AV junction and right ventricle. After every eighth atrial or ventricular driving beat (A1 or V1) at a constant cycle length, two successive atrial or ventricular premature beats (A2 and A3 or V2 and V3) were delivered. The A1A2 or V1V2 interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Theoretically, both retrograde conduction and retrograde concealed conduction may occur from the ventricles to the fibrillating atria via the accessory pathway, which may interfere with subsequent antegrade conduction from the atria to the ventricles. Retrograde concealed conduction in the preexcitation syndrome has been demonstrated using the extrastimulus techniques during sinus rhythm (12)(13)(14)(15), and its role during atrial fibrillation has also been inferred (16 Our data also showed an episode of retrograde invasion of the atrium during atrial fibrillation by wavefronts originating from atrioventricular node conduction (Fig. 5, panel 12), inhibiting accessory pathway activation by subsequent atrial wavefronts (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Theoretically, both retrograde conduction and retrograde concealed conduction may occur from the ventricles to the fibrillating atria via the accessory pathway, which may interfere with subsequent antegrade conduction from the atria to the ventricles. Retrograde concealed conduction in the preexcitation syndrome has been demonstrated using the extrastimulus techniques during sinus rhythm (12)(13)(14)(15), and its role during atrial fibrillation has also been inferred (16 Our data also showed an episode of retrograde invasion of the atrium during atrial fibrillation by wavefronts originating from atrioventricular node conduction (Fig. 5, panel 12), inhibiting accessory pathway activation by subsequent atrial wavefronts (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…It is possible that wavefronts that failed to activate the accessory pathway may have partially invaded the pathway, preventing subsequent excitation. Concealed antegrade conduction into the accessory pathway has been demonstrated with the atrial extrastimulus techniques during sinus rhythm, and has been proposed to explain the irregular pattern of preexcitation during atrial fibrillation (12,13). However, concealed conduction during atrial fibrillation has not been shown.…”
Section: Discussionmentioning
confidence: 99%